Physical Characteristics Of Sol-gel Derived SiO2 Thick Film on 4H-SiC. - Jo, Lene Tan; Kuan, Yew Cheong; Rusli, Rusli (2007)
The excellent properties of SiC have led to the usage of this material as a substrate for high power, high temperature, and high frequency metal-oxide-semiconductor (MOS)-based device applications [1,2,3].